Neoadjuvant chemotherapy plus radiation versus chemotherapy plus regional hyperthermia in high-grade soft tissue sarcomas: a retrospective comparison. (1st January 2019) - Zschaeck, Sebastian; Wust, Peter; Melcher, Ingo; Nadobny, Jacek; Rau, Daniel; Striefler, Jana; Pahl, Stefan; Flörcken, Anne; Kunitz, Annegret; Ghadjar, Pirus
Abstract: Purpose: Localized adult high-grade soft tissue sarcomas (STS) usually require multimodality treatment including surgery, radiotherapy, chemotherapy and hyperthermia. If maximal preoperative tumor-shrinkage is envisaged, neoadjuvant chemotherapy + radiation (CRT) is often applied, however at the expense of relatively high toxicities and increased postoperative complication rates. This study aims to compare preoperative CRT with neoadjuvant chemotherapy + regional hyperthermia (HCT) regarding histopathological response, toxicity and outcome. Methods: In this retrospective analysis, 61 consecutive high-grade STS patients treated between 2009 and 2016 were included. All patients were treated within a prospective treatment protocol. 28 patients received neoadjuvant CRT 33 patients HCT. CRT consisted of four cycles doxorubicin/ifosfamide and two cycles ifosfamide concomitant to 50.4 Gray external beam radiotherapy. HCT consisted of 4–6 cycles doxorubicin/ifosfamide with deep regional hyperthermia administered bi-weekly during each cycle. Association of treatment modality with overall survival (OS), local control (LC) and freedom from distant metastases (FFDM) was evaluated by Kaplan–Meier and log-rank analyses. Results: The overall patient characteristics were well balanced. Histopathological tumor response did not differ significantly between both groups ( p = .67), neither did higher-grade toxicities during neoadjuvant treatment. Wound dehiscence ( p = .018) and surgical hospital re-admissions ( p < .001) were both significantly more frequent in the CRT group. Two-year OS, LC and FFDM rates of all patients were 93, 85 and 71% with no significant differences between CRT and HCT. Conclusion: Compared to CRT, HCT seems equally efficient and appears to bear less surgical complications. Interpretation should be cautious due to the low number of patients and the retrospective nature of this study.